Analysis of the Braking Performance of the Hydraulic Retarder in Mining Dump Truck based on AMESim - Deng Lin (Jixie chuandong)
The hydrodynamic retarder is one of the important auxiliary braking system in mining dump truck,which has an important influence on the braking force distribution and braking performance of the vehicle. Taking the braking performance of the hydraulic retarder in DFD30 T mining dump truck as the study object. By using the simulation software AMESim,the brake whole model is built,and a retarder under different conditions are analyzed,the result of simulation is compared and analyzed,the further research of the hydraulic retarder braking performance of the system is carried out. Through studying the matching of retarder brake and service brake and simulation analysis of joint braking,it can be seen that the use of hydraulic retarder of brake force distribution,automobile braking performance,driving safety have certain superiority.